Extracting Interdisciplinary Criteria for Higher Education Curricula from the Documents and Ratifications - Mahdi Sobhaninejad, Soolmaz Nourabadi, (Opción, 2019)
The study has been organized to evaluate the focus on interdisciplinary criteria in the higher education curriculum in the Supreme Council of the Cultural Revolution of Iran via qualitative and documentary analysis with inferential and conceptual analysis. As a result, in Supplementary ratification No. 679 of Supreme Council of Cultural Revolution, attention has been paid to curriculum components that are clearly visible in this movement. In conclusion, interdisciplinary and intradisciplinary criteria have been used in the current and distinct sense of term, such as interdisciplinary tendencies in humanities, and intradisciplinary humanities with other sciences